2012
DOI: 10.1117/12.908583
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the volume ablation rate for metals at different laser pulse-durations from ps to fs

Abstract: Ultra short laser pulses in the ps or fs regime are used, when high requirements concerning machining quality are demanded. However, beside the quality also the process efficiency denotes a key factor for the successful transfer of this technology into real industrial applications. Based on the ablation law, holding for ultra short pulses with moderate fluences, it has been shown that the volume ablation rate can be maximized with an optimum setting of the laser parameters. The value of this maximum depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…Similar calculations have been done for a Gaussian shaped beam as emitted by most ultra short pulsed systems (Neuenschwander et al (2012), Neuenschwander et al (2010, Raciukaitis et al (2009)). Again a maximum removal rate per average power (ablation efficiency) is observed:…”
Section: Ablationmentioning
confidence: 85%
See 3 more Smart Citations
“…Similar calculations have been done for a Gaussian shaped beam as emitted by most ultra short pulsed systems (Neuenschwander et al (2012), Neuenschwander et al (2010, Raciukaitis et al (2009)). Again a maximum removal rate per average power (ablation efficiency) is observed:…”
Section: Ablationmentioning
confidence: 85%
“…Due to incubation effects the threshold fluence also strongly depends on the number of pulses applied, which is described for metals by Schmid et al (2011), Neuenschwander et al (2012, Jee et al (1988) and Mannion et al (2004). Additionally it was found that also the energy penetration depth shows an incubation effect of the same kind.…”
Section: Ablationmentioning
confidence: 95%
See 2 more Smart Citations
“…However, sub-picosecond pulses can further increase the ablation efficiency for certain materials, depending on the available average power and peak fluence as well as the desired feature size. On the one hand, for practical situations the efficiency generally changes little from 1 ps to 500 fs [3,4]. On the other hand, the situation may be different at harmonic wavelengths, where a careful optimization at high average power is challenging, in particular as frequency conversion is typically optimized for certain pulse durations and energies.…”
mentioning
confidence: 98%